(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Handwriting is often used as a reliable tool in forensic investigations, especially for verifying documents and identifying individuals. However, most handwriting samples are typically collected under normal seated writing conditions. In real-life situations, people may write under unusual postures, which can influence the way their handwriting appears. This study focuses on analyzing handwriting written in three specific postures: standing against a wall, lying down, and while travelling. Participants were asked to write a fixed text in each of these positions, and the resulting samples were examined for noticeable changes in writing features such as alignment, pressure, slant, size, and overall clarity. The objective was to observe how these postures impact handwriting and whether a person’s unique writing style still remains recognizable. The results showed that while certain visual aspects of handwriting changed due to discomfort or lack of stability, core individual traits were still identifiable. This highlights the need for forensic experts to consider writing posture as a factor during handwriting examination in non-standard scenarios.